Farm-heterogeneity and persistent and transient productive efficiencies in Ethiopia's smallholder cereal farming - Oumer Berisso; Almas Heshmati (IZA Journal of Development and Migration, 2020)
This paper does an empirical comparison of time-invariant and time-varying technical inefficiency measures obtained from an econometric estimation of different panel data stochastic production frontier models. It estimates four panel data specifications of frontier models widely used in empirical applications using a panel dataset from the Ethiopian cereal farming sector. The empirical results show that estimates of both the magnitude and the individual farms' rankings of persistent and transient productive efficiencies differ considerably across models and based on their agro-ecological zones location. The results further show that the cereal growing farms experience much more transient inefficiency as compared to persistent inefficiency.
Keywords: C23; D24; O13; Q18; 330; Stochastic frontier; heterogeneity; persistent and transient efficiency; cereal farming